Impact of short-term climatic events on latest Pliocene land settings and communities in Central Italy (Upper Valdarno basin) - Bertini, Adele; Magi, Maurizio; Mazza, Paul P. a; Fauquette, Séverine (Quaternary International, 2010)
The Upper Valdarno (Italy) Plio-Pleistocene continental deposits record the latest uniform subtropical humid conditions and the successive climatic signature of glacial/interglacial cycling. The palynological and sedimentological analyses on the Poggio Rosso alluvial plain sediments reveal two major climatic ﬂuctuations correlated to a glacial/interglacial cycle just before the Plio-Pleistocene boundary. The glacial phase, indicated by the expansion of herbs as well as by ephemeral streams associated with calcareous palaeosols, extends from the base of the succession and culminates close to an impressive mammalian bone accumulation dated at 1.87 Ma. The associated increasing aridity had severe consequences on the faunal communities, inducing the migration of open plain dwellers and the trapping of other residents around a few residual shrinking water bodies. A cooperative Pachycrocuta brevirostris clan acted as regulator of game populations debilitated by drought. Previous research indicates that hyenas were also the major bone accumulators. The following moister and warmer interglacial phase ca 1.83 Ma is documented by arboreal taxa and hydromorphic palaeosols in a ﬂoodplain crossed by migrating, perennial, sinuous streams. The Climatic Amplitude Method calculated mean annual temperatures around 12.5–14 C and mean annual precipitation around 800 mm, with a minimum of 400 mm during the glacial phase and 15/16–19 C and 750–1200 mm during the interglacial phase. The reconstruction reveals higher mean annual temperatures and precipitation during the interglacial as compared to the present-day climate. During the glacial, conditions were similar to today’s in all but lower precipitation values were reached during the acme drought phase just above the fossiliferous bed. Poggio Rosso documents the ecological consequences the buildup of the Apennine chain had under the effects of the latest Pliocene global climatic changes. It therefore represents one of the ﬁrst signals of the patchiness that, since then, gradually increased leading to the eventual habitat fragmentation typical of the late Pleistocene landscapes.
Keywords: climatic fluctuations; patchiness; Pleistocene landscapes (PG); Pollen analysis; sediment analysis